Sensory Characteristics and Consumer Preference for Cooked Chicken Breasts from Organic, Corn-fed, Free-range and Conventionally Reared Animals - Lawlor, J.B.; Sheehan, E.M.; Delahunty, C.M.; Kerry, J.P.; Morrissey, P.A. (International Journal of Poultry Science, 2003)
The sensory characteristics of cooked chicken breasts from organic (n=4), corn-fed (n=1), free range (n=5) and conventionally (n=5) reared animals from conventional origins were determined. Twelve trained assessors described the sensory characteristics of all samples using twenty-one attributes. One-way analysis of variance showed significant (P